Synergies in minority protection European and international law perspectives - Henrard, Kristin; Dunbar, Robert 1960- (Cambridge University Press, 2008)
There has recently been a remarkable growth in standard-setting with respect to the protection of minorities in international and European law. Layered on top of existing human rights standards relevant to minorities, these developments have resulted in a complex and multi-faceted regime, but one which still does not amount to an integrated and coherent system of minority protection. In addition to providing an up-to-date account of the relevant standards and their development in practice, this collection breaks new ground by seeking to identify the extent to which some integration and coherence (synergy) is emerging as a result of the work of treaty-monitoring bodies and other international institutions. Leading experts on the main instruments and institutions assess matters such as the application of similar principles, the emergence of common themes, explicit cross-referencing between treaty bodies and international institutions and the development of similar working methods